PROOXIDANT-ANTIOXIDANT HOMEOSTASIS IN BREEDING BOARS DEPENDING ON HOUSING CONDITIONS - Shostya, A. M.; Sarnavska, I. V.; Tenditnyk, V. S.; Kuzmenko, L. M.; Slynko, V. G.; Shаferivskiy, B. S. (Scientific Progress & Innovations, 2020)
The sex activity of boars is largely influenced by housing conditions, feeding and the intensity of using. The limiting parameters for housing breeding boars include temperature in the pen. Usually in summer and winter, these animals are under temperature stress, which is accompanied by the acceleration of peroxidation processes, reduced quality of sperm and its fertilizing ability. The aim of the research was to study the peculiarities of forming pro-oxidant-antioxidant homeostasis in breeding boars under temperature stress conditions. 6 adult boars of Myrhorod breed, aged from 18 to 24 months were used in the experiment. The experiment lasted 120 days, including: preparatory period – 30 days, the main period – 60 days (feeding vitamin A, vitamin E, ascorbic acid) and final – 30 days. The level of the above-mentioned biologically active components in the diet of the second experimental group was 10 % higher as compared with the control group. The received ejaculates were examined according to standard parameters, and the intensity of peroxidation in the sperm plasma and sperm of breeding boars was determined. The quality of sperm production in breeding boars was significantly affected by the temperature regime of their housing. The keeping of animals in pens with higher temperature was accompanied by a decrease in ejaculate volume by 7.5 %, concentration by 12 % and survival ability – by 16.0 %. Such changes occurred against the background of increased activity of SOD, catalase and TBA-active compounds in sperm and sperm plasma, as well as a decrease in saturation of ascorbic acids (p<0.05… p<0.001) and vitamin E. Housing breeding boars in a pen with lower temperature was accompanied by 7.7 %, decrease in ejaculate volume, the total amount of semen – by 17.4% and their survival ability – by 17.5 %. The reason for deteriorating the quality of sperm production is the acceleration of peroxidation processes – the accumulation of TBA-active compounds amount in the semen and sperm plasma. The introduction of water-soluble vitamin forms of antioxidant action in the main diet for breeding boars under high and low temperatures positively affects sperm production indexes: the increase in ejaculate volume, sperm concentration and survival ability. Feeding vitamin supplements to breeding boars increases the amount of vitamins A and E in the semen and sperm plasma, reduces the content of ascorbic and dehydro-ascorbic acids, stimulates the activity of SOD and catalase, and inhibits the processes of peroxide oxidation reducing TBA-active compounds (p<0.05).